2021
DOI: 10.1063/5.0047512
|View full text |Cite
|
Sign up to set email alerts
|

On the noise reduction of a porous trailing edge applied to an airfoil at lifting condition

Abstract: Paper published as part of the special topic on Special Issue on the Lattice Boltzmann Method This paper was selected as Featured This paper was selected as Scilight ARTICLES YOU MAY BE INTERESTED INAn interpretable framework of data-driven turbulence modeling using deep neural networks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…2018; Teruna et al. 2020, 2021). The cross-spectrum density (CSD) between two pressure signals at two locations is defined as The coherence refers to the normalized amplitude for the CSD, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2018; Teruna et al. 2020, 2021). The cross-spectrum density (CSD) between two pressure signals at two locations is defined as The coherence refers to the normalized amplitude for the CSD, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the most vital noise sources are mainly located near the trailing edges. In order to study the detailed distribution of the noise sources on the airfoil and its influence on the far-field noise, we divide the airfoil surface, including the serrated surface, into many strips (Avallone et al 2018;Teruna et al 2020), as illustrated in figure 16. Here, we are mainly concerned with the influence of a fully developed area, and the surface with x/l > 0.5 is split into many spanwise strips.…”
Section: The Influence Of Serrations On Dipole Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruneau et al [26] demonstrated that partial porous coatings can reduce drag on Ahmed bodies by up to 45%. Teruna et al [27] showed that a porous trailing edge on a NACA0018 aerofoil can reduce aerodynamic noise by up to 7 dB. Porous coatings have also been studied for reducing noise produced by vortex shedding for bluff bodies such as cylinders, as well as reducing their drag coefficients in certain cases.…”
Section: Porous Coatingsmentioning
confidence: 99%
“…Porous materials Similar to serrations, porous materials can be integrated into the structure of an airfoil to mitigate both self-noise [12][13][14] and turbulence-interaction noise [15][16][17][18]. At the leading edge, one possible mitigation mechanism for the turbulence-interaction noise is related to the damping of the deformation that is experienced by the turbulent vortices impinging on the airfoil surface.…”
Section: A Reduction Of Noise At the Sourcementioning
confidence: 99%